Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(m^6+n^4=\left(m^3\right)^2+2.m^3.n^2+\left(n^2\right)^2-2m^3n^2\)
\(=\left(m^3+n^2\right)^2-\left(\sqrt{2m^3}n\right)^2\)
\(=\left(m^3+n^2-\sqrt{2m^3}n\right)\left(m^3+n^2+\sqrt{2m^3}n\right)\).
\(x^2-y^2+4x+4\)
\(=\left(x+2\right)^2-y^2\)
\(=\left(x+2+y\right)\left(x+2-y\right)\)
\(4x^2-y^2+8\left(y-2\right)\)
\(=4x^2-\left(y^2-8y+16\right)\)
\(=4x^2-\left(y-4\right)^2\)
\(=\left(2x+y-4\right)\left(2x-y+4\right)\)
x6+3x4y2-8x3y3+3x2y4+y6= x6+3x4y2+3x2y4+y6-8x3y3=(x2+y2)3-(2xy)3
= (x2+y2-2xy)[(x2+y2)2+2xy(x2+y2)+(2xy)2]= (x-y)2(x4+6x2y2+y4+2x3y+2xy3)
(x2+y2-5)2-4x2y2-16xy-16=(x2+y2-5)2-(4x2y2+16xy+16)=(x2+y2-5)2-(2xy+4)2
=(x2+y2-5+2xy+4)(x2+y2-5-2xy-4)=(x2+2xy+y2-1)(x2-2xy+y2-9)=[(x+y)2-1][(x-y)2-32]=(x+y-1)(x+y+1)(x-y-3)(x-y+3)
x4+324=x4+36x2+324-36x2=(x2+18)2-(6x)2=(x2+18-6x)(x2+18+6x)
= x^8 - x^7 + x^6 - x^5 + x^4 + x^7 - x^6 + x^5 - x^4 + x^3 + x^6 - x^5 + x^4 - x^3 + x^2 + x^5 - x^4 + x^3 - x^2 + x + x^4 - x^3 + x^2 - x + 1
= (x^8 - x^7 + x^6 - x^5 + x^4) + (x^7 - x^6 + x^5 - x^4 + x^3) + (x^6 - x^5 + x^4 - x^3 + x^2) + (x^5 - x^4 + x^3 - x^2 + x) + (x^4 - x^3 + x^2 - x + 1)
= x^4(x^4 - x^3 + x^2 - x + 1) + x^3(x^4 - x^3 + x^2 - x + 1) + x^2(x^4 - x^3 + x^2 - x + 1) + x(x^4 - x^3 + x^2 - x + 1) + (x^4 - x^3 + x^2 - x + 1)
= (x^4 + x^3 + x^2 + x + 1)(x^4 - x^3 + x^2 - x + 1)
2222222222222222222222222222222222222222222222222222222222223333333